La evaluación de impacto de la formación doctoral. Experiencia del CEPES de la Universidad de La Habana. - López Domínguez, Abelardo (2023)
The work presented addresses the process of evaluating the impact of doctoral training from a theoretical perspective, with exemplification of the results of this area at the Center for Studies for the Improvement of Higher Education (CEPES) of the University of Habana. The article intends to take part, from the theoretical, of the meaning of the impact evaluation of doctoral training processes, while exposing the essential results achieved by CEPES in this direction. Likewise, it also seeks as a general objective: Reflect the importance of impact evaluation in the doctoral training process and its follow-up from interdisciplinary in Educational Sciences. Fundamentally supported by theoretical and empirical methods and the authors' own experience in the doctoral training process.